2022
DOI: 10.3390/ijerph19073926
|View full text |Cite
|
Sign up to set email alerts
|

A Fresh Look at Mouthwashes—What Is Inside and What Is It For?

Abstract: Mouthwashes are a very popular additional oral hygiene element and there are plenty of individual products, whose compositions are in a state of flux. The aim of our study was to investigate the compositions of mouthwashes and their functions, as well as to discuss their effectiveness in preventing and curing oral diseases and side effects. We searched for mouthwashes available on the market in Poland. We identified 241 individual mouthwash products. The extraction of compositions was performed and functions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 159 publications
(132 reference statements)
1
20
0
Order By: Relevance
“…Regarding the use of fluorinated products, mouthwashes are a very popular additional oral hygiene element [27,28], and in our study, a good percentage was found to use them together with a fluoride toothpaste, with high satisfaction regarding it.…”
Section: Discussionsupporting
confidence: 55%
“…Regarding the use of fluorinated products, mouthwashes are a very popular additional oral hygiene element [27,28], and in our study, a good percentage was found to use them together with a fluoride toothpaste, with high satisfaction regarding it.…”
Section: Discussionsupporting
confidence: 55%
“…Besides, the lower antifungal activity found in herbal mouth rinses might be due to uncertainty on the effectiveness of active ingredients and their properties on two Candida species. In addition, it could be assumed that some of the components associated with the active ingredients may present no effects (medical or pharmaceutical) and are used only for marketing purposes (Radzki et al, 2022). Furthermore, there is also a possibility of differences between the declared and actual composition of a product, which may alter the characteristics and functions of the substances in the herbal mouth rinses tested in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been a growing surge in research investigating the constituents of mouthwashes. Whilst studies examining the ingredients of toothpastes have been conducted in Turkey 16 and mouthwashes in Poland, 17 no previous research has explored the composition of commercially available mouthwashes in the Turkish market. In this context, the present study is an innovative and pioneering approach where the contents of mouthwashes are comprehensively examined and presented for the first time.…”
Section: Introductionmentioning
confidence: 99%